Ellipsometric plasmon sensor for adsorbed layers on thin Ag and Au films - Severynov, V.L.; Shaikevich, I.A.; Shybiko, Y.A. (Functional Materials, 2005)
Using Kretschmann’s method, important parameters defining the propagation of surface waves (namely, the restored polarization azimuth ψ and phase difference Δ between p- and s-components of the electromagnetic wave) versus the light incidence angle θ for thin Ag and Au films have been investigated. It has been show that at wavelength λ = 620 nm, the ellipsometric sensor on Au film is more sensitive to molecular pollutions than sensor on Ag film. Используя метод Кречмана, исследованы угловые зависимости поляризационных параметров (азимут ψ восстановленной линейной поляризации и сдвиг фаз Δ между р- и s-компонентами поляризации электромагнитной волны) для тонких пленок Ад и Au. Показано, что на длине волны λ = 620 нм эллипсометрический сенсор, изготовленный на пленке золота, является более чувствительным к молекулярным загрязнениям, чем на пленке серебра. З застосуванням метода Кречмана досліджено кутові залежності поляризаційних параметрів (азимут ψ відновленої лінійної поляризації та зсув Δ фаз між р- та s-компонентами електромагнітної хвилі) для тонких плівок Ад та Au. З цих даних видно, що на довжині хвилі λ = 620 нм еліпсометричний сенсор, виготовлений на плівці золота, має вищу чутливість до молекулярних забруднень, ніж сенсор на плівці срібла.